IMPLEMENTASI MODEL SOSIODRAMA DALAM MENINGKATKAN SIKAP NASIONALISME MAHASISWA PADA MATA KULIAH PENDIDIKAN PANCASILA - Noervadila, Irma; Surur, Miftahus; Anam, Syaiful (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This research has one of the most important goals, namely increasing nationalism among students, considering that in the results of observations students are mutually indifferent to their friends, in this case if in class or outside the class they are indifferent to their friends and it is difficult to collaborate well between friends. This study included quantitative research with research subjects namely economics class semester 1 of the economics education study program, totaling 34 students. This research is a pre-experimental study, in which the assessment is in the form of a One Group Pre-Test Post-Test which is carried out in only one class without a control class. The analytical method used is inferential statistics where in this statistic the results are used to generalize the population. In this study we used the t test to test the hypothesis. From the results of the research that has been carried out, a conclusion can be drawn that the implementation of the sociodrama method can increase the attitude of nationalism or the attitude of loving the homeland of students in Pancasila education courses.